Disorders Associated With Diverse, Recurrent Deletions and Duplications at 1q21.1 - Pang, Hui; Yu, Xiaowei; Kim, Young Mi; Wang, Xianfu; Jinkins, Jeremy K.; Yin, Jianing; Li, Shibo; Gu, Hongcang (Frontiers in Genetics, 2020)
The subchromosomal region 1q21.1 is one of the hotspots in the human genome for deletions and reciprocal duplications, owing to the existence of hundreds of segmental duplications. Recurrent deletions and duplications in this region are thought to be causative in patients with variable clinical manifestations. Based on the genomic locations, deletions and duplications at the 1q21.1 locus have been associated with distinguishable syndromes: chromosome 1q21.1 deletion syndrome, chromosome 1q21.1 duplication syndrome, and thrombocytopenia-absent radius (TAR) syndrome, which is partially due to deletions at the proximal 1q21.1 region. We report here diverse, recurrent deletions and duplications at the 1q21.1 locus in 36 patients from a cohort of 5,200 individuals. Among the 36 patients, 18 patients carry 1q21.1 deletions, nine individuals have reciprocal duplications at 1q21.1, two patients share an identical short deletion, and the remaining seven possess variable sizes of duplications at the proximal 1q21.1 region. Furthermore, we provide cytogenetic characterization and detailed clinical features for each patient. Notably, duplications at the proximal 1q21.1 region have not been associated with a defined disorder in publications. However, recurrent duplications at the proximal 1q21.1 region among the seven patients strongly suggested that the variants are likely pathogenic. The common phenotypical features of those disorders are also summarized to facilitate clinical diagnoses and genetic counseling.